Variability in Distillers’ Co-Product Compositions and Their Nutritional Availability for Pigs: Insights from a Systematic Literature Review - Rech, Herbert; Zem Fraga, Alícia; Haubert Franceschi, Carolina; Bonadiman Mariani, Alexandre; Romeiro de Oliveira, Caroline; Miotto Galli, Gabriela; Létourneau-Montminy, Marie-Pierre; Hauschild, Luciano [UNESP]; Bertol, Teresinha Marisa; Andretta, Ines (MDPI, 2024)
This study aimed to examine the nutritional diversity of distillers’ co-products in pigs. Two distinct databases were used in this study. The first was compiled through a systematic review of previous scientific publications that have evaluated the chemical composition and nutritional availability of these ingredients for pigs. The final database included information collected from 49 studies published between 2003 and 2022. Most of the studies focused on distillers’ co-products produced from corn (90%) and assessed dried distillers grains with solubles (DDGS; 92%). A wide variety of nutritional compositions was observed in the selected studies, with coefficients of variation of 8% for gross energy and 13% for crude protein in dried distillers grains (DDGs). In the general database, half of the studies were published from 2003 to 2015 and the other half from 2015 to 2022. Greater variability in the net energy content and standardized ileal digestible lysine concentrations from 2015 to 2022 were the main concerns. The second database included information on high-protein dried distillers grains (HP-DDGs) collected directly from several feed mills and was built using the results of chemical analyses. These results suggest that the nutritional matrix of co-products should be assessed for each processing plant. Nevertheless, a coefficient of variation of up to 6% was found for crude protein and up to 20% for ether extract. Variability in nutritional composition is an important challenge of using distillers’ co-products in pig feed.
Keywords: amino acids; DDGS; dried distillers grains with solubles; energy; feed ingredient; precision nutrition; swine